2015
DOI: 10.17576/jkukm-2015-27-09
|View full text |Cite
|
Sign up to set email alerts
|

Pemodelan Hubungan Antara Kualiti Perkhidmatan, Kesan Alam Sekitar, Sikap dan Keinginan untuk Menggunakan Park-and-Ride

Abstract: ABSTRAKPemodelan persamaan struktur (SEM) Structural equation modelling (SEM) is a modelling technique that can handle a large number of endogenous and exogenous variables, as well as latent variables specifi ed as linear combinations of the observed variables. Usually, the estimation method used in the modelling analysis is the maximum likelihood (ML) estimation. In this study, the park-and-ride (P&R) usage model was developed to estimate the direct effects, indirect effects and overall impact on the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Furthermore, a study by Nkurunziza et al [35] recorded that the perceived barrier had a significant impact on cycling behaviour. This finding was in line with the result from the study predicting the behavioural attempt of using the Park & Ride service [46]. Meanwhile, the perceived barrier element was found to be connected to an individual's motivation to use the bicycle, as reported in several previous studies on the same subject studies [35,42,43].…”
Section: Perceived Barriersupporting
confidence: 89%
“…Furthermore, a study by Nkurunziza et al [35] recorded that the perceived barrier had a significant impact on cycling behaviour. This finding was in line with the result from the study predicting the behavioural attempt of using the Park & Ride service [46]. Meanwhile, the perceived barrier element was found to be connected to an individual's motivation to use the bicycle, as reported in several previous studies on the same subject studies [35,42,43].…”
Section: Perceived Barriersupporting
confidence: 89%
“…This has resulted in users having to drive directly to their workplace instead of using the P&R facility. The service provider of P&R facilities could also consider the proposal made by Borhan et al [20] and Lam et al [18] to increase the use of P&R facilities in Putrajaya, i.e., providing a good public bus service, providing free parking or charging a small parking fee at P&R facilities, and a reasonable bus fare. As asserted by Madha et al [38], belief is "the basis for loyalty."…”
Section: Discussionmentioning
confidence: 99%
“…Even though the world literature has reported many benefits of using P&R facilities [4,10,11,16], car drivers in Malaysia are still not persuaded to use the facilities. Borhan et al [19,20], Norhisham et al [21], and Syed Adnan and Kadar Hamsa [22] have demonstrated that the utilisation rate of P&R facilities is relatively low. According to Borhan et al [19,20], this underutilisation is due to several factors, such as an unsuitable location of the P&R lots, low quality public transit, and high parking fees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways to achieve sustainable mobility and transportation development in urban areas is by encouraging LRT usage. Even though the public is aware of the significance of sustainable transportation, most of them still exhibit limited structural behavior aimed at transportation sustainability [13,14], which is evident by the lower public acceptance of public transportation as a commuting alternative [15][16][17][18]. Despite the fact the government and authorities strongly encourage the use of public transport, the response from the public is still disappointing.…”
Section: Introductionmentioning
confidence: 99%